ANALISIS PEMANFAATAN UMPAN BALIK DALAM PEMBELAJARAN TERDIFERENSIASI DI FASE C SEKOLAH DASAR - Intan Budi Komara; Rina Heryani; Faisal Sadam Murron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The utilization of student feedback in differentiated instruction plays a critical role in supporting adaptive teaching strategies that meet individual learning needs. However, in practice, this aspect is often not fully optimized. This study aims to analyze the forms of feedback delivery, the differences in feedback characteristics, and the teacher's strategies in responding to student feedback within the context of differentiated learning at Phase C of Primary School. The study employed a descriptive qualitative method with a case study approach. Data were collected through classroom observations, interviews, and open-ended questionnaires involving one teacher and 17 sixth-grade students at a public elementary school in Sukabumi City, Indonesia. The findings reveal that students provided feedback in both informal oral forms and written formats, including manual and digital submissions. Distinct feedback characteristics were identified based on students’ levels of understanding: lower-level students requested visual aids, mid-level students suggested collaborative strategies, and higher-level students offered ideas such as grouping based on learning pace and task personalization. The teacher responded to the feedback by adjusting instructional processes—such as teaching pace, methods, and mediabut had not yet implemented differentiaion in content or product. While the teacher’s feedback responses were generally responsive and fostered student participation, they were not yet systematically structured. This study emphasizes that student feedback is an essential foundation for developing responsive differentiated instruction centered on individual learning readiness.